PERFORMANCE INDICATORS AND BUSINESS INTELLIGENCE TOOLS APPLIED TO DRINKING WATER QUALITY IN THE FIELD OF REGULATION - de Melo, Rodrigo Antonio Pinto; Maia, Jane Carla Marinho de Souza; Soares, Cícero Henrique Macêdo; Gomes, Emanuele Ferreira; da Silva, Rafael Lima (Seven Editora, 2026)
In the context of exposure regulation, a system of performance indicators combined with Extraction, Transformation, and Loading (ETL) methods, coupled with dashboard analysis, is an important tool for evaluating the performance of a product's quality. Therefore, this work aims to present the functionalities and applications of a performance indicator system implemented for evaluating the quality of drinking water, considering parameters that demonstrate the effectiveness of the product's quality. The indicator evaluation system was built using an ETL process of the data, executed by Microsoft Power BI®, as it offers excellent functionalities for developing dashboards and devices that promote transparency and interaction mechanisms. It was possible to evaluate and analyze the quality of drinking water at production points and in the distribution network with the aid of graphic elements related to effectiveness and efficiency. Tools such as performance papers and data download options were made available on the dashboard, promoting transparency and joint participation by users and key stakeholders in basic sanitation management. Finally, the tool allowed for a comparison of the water quality performance produced at Water Treatment Plants (WTPs) with the targets established in Municipal Basic Sanitation Contracts or Plans (PMSB), and for directing inspections when the result was unsatisfactory.DOI: https://doi.org/10.56238/sevened2026.008-026